Problem zanieczyszczenia wód śródlądowych substancjami chemicznymi w świetle prawa europejskiego oraz prawa krajowego – uwagi krytyczne: [The problem of inland water pollution with chemical substances in the light of European and national law - critical remarks] (Studia Prawnicze / The Legal Studies, 2018)
Uchwalenie w 2017 r. nowej ustawy Prawo wodne nie rozwiązało wszystkich problemów związanych z wdrażaniem tych przepisów ramowej dyrektywy wodnej, których celem jest zapobieganie zanieczyszczeniom wód substancjami chemicznymi. W artykule wskazano na przyczyny tych trudności – zewnętrzne i wewnętrzne. Te pierwsze dostrzeżono w cechach regulacji europejskiej, takich jak jej fragmentaryczność i rozproszenie. Przyczyny wewnętrzne to legislacyjne usterki polskiej ustawy z 2017 r. Jej przepisom zarzucić można przede wszystkim brak precyzji i konsekwencji w rozgraniczaniu funkcji prawnych przypisanych substancjom szkodliwym oraz substancjom priorytetowym, nadto nadmierny rygoryzm. The adoption of the new Water Law in 2017 did not solve all problems related to the implementation of those provisions of the Water Framework Directive, which aim to prevent water pollution with chemical substances. The article indicates the external and internal reasons for these difficulties. The former lie in the features of European regulation, such as its fragmentation and dispersion. Internal reasons are legislative defects of the Polish act from 2017. Its provisions can be criticized primarily for the lack of precision and consistency in the delimitation of legal functions assigned to both hazardous substances and priority substances, and also excessive rigor.